Tindak Tutur Ilokusi Dalam Series Kalau Jodoh Takkan Kemana Season 2 di Youtube Indosat Ooredoo Hutchison - Nurkhofifah, Nanda (Peneliti.net, 2025)
This research aims to find out and describe the form of illocutionary speech acts in the series “If Your Soulmate Will Not Go Where” Season 2 in episode 1 on the Indosat Ooredoo Hutchison Youtube channel. The research method used in this research is a qualitative descriptive method. Research data was analyzed using skillful free-involved listening and note-taking techniques. The total research analysis data amounted to 15 data, namely assertive (declaring) illocutionary speech acts with 4 data, directives (ordering 1 data, commanding 2 data, begging 1 data, advising 1 data), expressive (apologizing 1 data, blaming 1 data, praising 3 data), and commissive (offering something) with 1 data.